A weakness determination and analysis model for business process improvement - Coskun, Semih; Basligil, Huseyin; Baracli, Hayri (EMERALD GROUP PUBLISHING LTD, 2008)
Purpose - Modeling of the methods for providing improvements in business processes by value adding is researched with an integrated approach. The main purpose in this approach is improving the processes by determining and analyzing the weak points and reducing the weakness degrees. Design/methodology/approach - The designed model determines weak points that need to be improved, analyzes them to find privileged processes in improvement by considering improvement costs and obtains the improvement degrees for defining the improvement strategy by four-phase business process improvement framework: start-up, self analysis, defining improvement strategy for making changes, feedback, and continuous improvement. Findings - The key factor in keeping up with changes in market conditions is systematic application of improvement efforts and providing planned and controlled value addition with these improvements. Decision problems in process improvement can be structured to provide input data suitable for multi-criteria decision making techniques and results meet the solution expectations. Research limitations/implications - The reason for using analytical hierarchy process, goal programming, and linear programming model is to select the process and determine its improvement degree. Solving the decision problems by these techniques is a time consuming process, so forming suitable programs with decision support systems will be useful. Practical implications - The theoretical structure of the modeled techniques in this study was examined with an industrial application. The application process and the results suitability were determined. Originality/value - The proposed model shows improvement amounts according to the amount of defined importance degrees. It presents an advantage to decision makers by giving concrete improvement values from model results determining their improvement strategies.
Keywords: Business improvement; Continuous improvement; Decision making; METHODOLOGY; Business & Economics